2019
DOI: 10.3390/antiox8090360
|View full text |Cite
|
Sign up to set email alerts
|

Lyophilized Maqui (Aristotelia chilensis) Berry Induces Browning in the Subcutaneous White Adipose Tissue and Ameliorates the Insulin Resistance in High Fat Diet-Induced Obese Mice

Abstract: Maqui (Aristotelia Chilensis) berry features a unique profile of anthocyanidins that includes high amounts of delphinidin-3-O-sambubioside-5-O-glucoside and delphinidin-3-O-sambubioside and has shown positive effects on fasting glucose and insulin levels in humans and murine models of type 2 diabetes and obesity. The molecular mechanisms underlying the impact of maqui on the onset and development of the obese phenotype and insulin resistance was investigated in high fat diet-induced obese mice supplemented wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
46
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 120 publications
(157 reference statements)
2
46
1
Order By: Relevance
“…Part of the anthocyanins metabolic effects occur by regulating adipogenesis, increasing FAO, lipolysis, thermogenesis and mitochondrial biogenesis, regulating satiety and reducing lipogenesis in different tissues and organs and enhancing energy expenditure and body weight progression [ 74 , 75 , 76 , 80 , 81 , 82 , 83 ] Dietary supplementation with anthocyanins improves the lipid profile by favorably controlling the circulating levels of TG, total cholesterol, LDL-cholesterol and HDL-cholesterol [ 84 ].…”
Section: Anthocyaninsmentioning
confidence: 99%
“…Part of the anthocyanins metabolic effects occur by regulating adipogenesis, increasing FAO, lipolysis, thermogenesis and mitochondrial biogenesis, regulating satiety and reducing lipogenesis in different tissues and organs and enhancing energy expenditure and body weight progression [ 74 , 75 , 76 , 80 , 81 , 82 , 83 ] Dietary supplementation with anthocyanins improves the lipid profile by favorably controlling the circulating levels of TG, total cholesterol, LDL-cholesterol and HDL-cholesterol [ 84 ].…”
Section: Anthocyaninsmentioning
confidence: 99%
“…The improvement in fibroblast growth factor 21 signaling was also involved in the beneficial effects of Maqui berry supplementation. The results found that the intervention of Maqui berry could improve high-fat-diet-induced obesity and associated illnesses [ 73 ] ( Table 2 ).…”
Section: Anthocyanins and Obesitymentioning
confidence: 99%
“…Regarding the beneficial health effects of maqui berry, anti-inflammatory [10] [11] [12] [13], anti-diabetic [14], antidepressant [15], anti-obese [16], and memory improving [17] effects have been reported. Moreover, we previously confirmed that maqui berry extract (MBE) possesses excellent ameliorating effects against dry eyes in animal models [18] and clinical trials [19] [20] with Japanese subjects.…”
Section: Introductionmentioning
confidence: 99%